QUANTITATIVE INDICATORS OF COPPER-RESISTANT MICROORGANISMS DISTRIBUTION IN NATURAL ECOSYSTEMS - Havryliuk, Olesia; Hovovrukha, Vira; Sachko, Anastasiia; Gladka, Galina; Tashyrev, Oleksandr (My University, 2021)
Copper is a highly toxic metal common in both natural and man-made ecosystems. The goal of the work was to determine the level of resistance of microorganisms of natural ecosystems to cationic form and organometallic complex of Cu2+. Microorganisms of 9 natural ecosystems of five geographic zones (the Antarctic, the Arctic, the Dead Sea (Israel), middle latitude (Ukraine) and the equatorial zone of South America (Ecuador) were investigated. Resistance of microorganisms was determined by cultivation in the medium with concentration gradient of Сu2+. The amount of Cu2+-resistant microorganisms in natural ecosystems was determined by colony counting on nutrient agar with Сu2+ citrate and Cu2+ cation. The Cu(II) concentration in soil and clay samples was analyzed by atomic absorption spectroscopy method. We have confirmed the hypothesis that microorganisms resistant to toxic Cu2+ compounds in high concentrations exist in any natural ecosystem. The resistance to Cu2+ cation was 8 – 31 and 14 –140 times less than to Cu2+ citrate in nutrient and mineral agar media respectively. The amount of Cu2+-resistant microorganisms in natural ecosystems reached hundreds and thousands at the presence of 175…15 500 ppm Cu2+. Thus, the soils, clays and sands of natural ecosystems are a “genetic resource” of copper-resistant microorganisms that are promising for development of novel biotechnology of purification of copper-containing wastewater and soil bioremediation.
Keywords: copper pollution; copper-resistant microorganisms; natural ecosystems; environmental biotechnologies